2018
DOI: 10.1088/1361-6528/aacd75
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser-induced size reduction and emission quantum yield enhancement of colloidal silicon nanocrystals: effect of laser ablation time

Abstract: Colloidal silicon (Si) nanocrystals (NCs) with different sizes were successfully prepared by femtosecond laser ablation under different laser ablation time (LAT). The mean size decreases from 4.23 to 1.42 nm by increasing the LAT from 30 to 120 min. In combination with structural characterization, temperature-dependent photoluminescence (PL), time-resolved PL and PL excitation spectra, we attribute room-temperature blue emissions peaked at 405 and 430 nm to the radiative recombination of electron-hole pairs vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Generally, the prolonged ablation time results in a smaller particle size and improved photoluminescence quantum yield. 260 The solvent-dependent sizes of silicon QDs were also demonstrated in a recent work, where silicon QDs were synthesized in six different organic solvents (1-octyne, 1-octanol, 1-hexanol, 2-propanol, methanol, and ethanol). 261 The smallest size was obtained in 1-octyne, and the size increased with a decrease in the alkyl-chain length in the alcohols.…”
Section: Multi-dimensional Design and Materials Science Of Silicon-co...mentioning
confidence: 69%
“…Generally, the prolonged ablation time results in a smaller particle size and improved photoluminescence quantum yield. 260 The solvent-dependent sizes of silicon QDs were also demonstrated in a recent work, where silicon QDs were synthesized in six different organic solvents (1-octyne, 1-octanol, 1-hexanol, 2-propanol, methanol, and ethanol). 261 The smallest size was obtained in 1-octyne, and the size increased with a decrease in the alkyl-chain length in the alcohols.…”
Section: Multi-dimensional Design and Materials Science Of Silicon-co...mentioning
confidence: 69%
“…The low monodispersity and low stability of the resulting quantum dots are the main limitations of the method. Nevertheless, it was recently shown that, when extending the femtosecond laser ablation time from 30 to 120 min, the size of the SiQDs formed in 1-octene varied from 4.2 to 1.4 nm, with measured PL quantum yield going from 23.6 to 55.8% (Zhang et al, 2018).…”
Section: Laser Generationmentioning
confidence: 99%
“…In 2000, Pavesi et al first reported on the nc-Si optical gain and stimulated emission at room temperature, and it is expected to become an efficient luminescent material [ 6 ]. Obtaining more suitable Si-based luminescent materials and improving the related fluorescence quantum efficiency has been one of the most difficult tasks in this field for more than two decades [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%